A preliminary survey of issues of Shiism in Malaysia with special reference to the state of Malacca - Jantan, Hamzah; Mohd Amin, Wan Mohd Azam; Awang Abd. Rahman @ Jusoh, Amilah (IIUM Press, International Islamic University Malaysia, 2018)
his paper offers an introductory discussion of Shiism as one of the sect in Muslim schism. It includes the historical development of Shiism in Muslim traditions whose influence can be traced in Malaysia, specifically in Malacca. The author emphasises the clear distinction between the Shiite and the Ahl al-Bayt, and some issues of Shiism that drew the attention of religious authority in Malacca. A qualitative methodology that includes the textual analysis and interview method were employed to analyse textual materials related to Shiism. Findings shows that Malay Shiites group existed in Malacca as most of them were inspired by the Iranian revolution on 1979.